HGG-17. HIGH-GRADE GLIOMA IN VERY YOUNG CHILDREN; A SINGLE-CENTER 11-YEAR-EXPERIENCE. (4th December 2020) - El-ayadi, Moatasem; Shawky, Omar; Naguib, Eman; Maher, Eslam; Abdelaziz, Amal; Ahmed, Soha; Refaat, Amal; von Bueren, André O; Taha, Hala; El-naggar, Shahenda; El-beltagy, Mohamed
Abstract: BACKGROUND: Data about high-grade glioma (HGG) in very young children (≤3 years old at diagnosis) is scarce. METHODS: 180 pediatric HGG patients were treated at the Children Cancer Hospital - Egypt (CCHE-57357) between July 2007 and June 2018, with 17 patients aged ≤3 years at diagnosis. Medical records were retrospectively reviewed for clinical, radiological and histopathological data, treatment received and survival outcome. RESULTS: Median age was 29.2 months (range: 2.4 – 35.8 months; males = 9). Most frequent pathological diagnosis was Glioblastoma, WHO grade-IV (n = 11, 64.7%) and one patient had H3-mutant diffuse midline glioma. All patients underwent surgery (gross-total resection, n = 6, 35.3%; subtotal-resection, n = 5, 29.4%; biopsy, n = 6, 35.3%). One patient (age = 7 months) progressed and died before starting adjuvant therapy. All patients ≤1 year of age (n = 5) received adjuvant chemotherapy (CT) only, older children (n = 11) received adjuvant radiotherapy (RT) (total dose range: 54 – 60 Gy) and CT (CCG-945 protocol). The 1-year overall survival (OS) rate was 47.1%; and event-free survival (EFS) rate was 35.3%. EFS differed between those who received RT and those who did not (1-year EFS 54.5% and 0% respectively, p = 0.001). Compared to older children, anatomical distribution of tumors was significantly different with non-midline locations being the commonest in patients ≤3 years old (88.2% vs 46.4%, p=0.01). CONCLUSIONS: HGG in very young children arise predominantly in non-midline locations and usually lack the H3-mutation. RT seems crucial in the management of pHGG regardless of age subgroup.